Combining information to estimate adherence in studies of pre‐exposure prophylaxis for HIV prevention: Application to HPTN 067. (25th January 2022) - Hughes, James P.; Williamson, Brian D.; Krakauer, Chloe; Chau, Gordon; Ortiz, Brayan; Wakefield, Jon; Hendrix, Craig; Amico, K. Rivet; Holtz, Timothy H.; Bekker, Linda‐Gail; Grant, Robert
Abstract : In trials of oral HIV pre‐exposure prophylaxis (PrEP), multiple approaches have been used to measure adherence, including self‐report, pill counts, electronic dose monitoring devices, and biological measures such as drug levels in plasma, peripheral blood mononuclear cells, hair, and/or dried blood spots. No one of these measures is ideal and each has strengths and weaknesses. However, accurate estimates of adherence to oral PrEP are important as drug efficacy is closely tied to adherence, and secondary analyses of trial data within identified adherent/non‐adherent subgroups may yield important insights into real‐world drug effectiveness. We develop a statistical approach to combining multiple measures of adherence and show in simulated data that the proposed method provides a more accurate measure of true adherence than self‐report. We then apply the method to estimate adherence in the ADAPT study (HPTN 067) in South African women.